Association between platelet reactivity and circulating platelet-derived microvesicles in patients with acute coronary syndrome. (14th July 2014) - Kafian, Sam; Mobarrez, Fariborz; Wallén, Håkan; Samad, Bassem
Abstract: High on-treatment platelet reactivity (HPR) to clopidogrel has been shown to increase the risk of cardiovascular events. Platelet-derived microvesicles (PMVs) may be prothrombotic and contribute to the risk of recurrent events observed in patients with HPR. However, PMVs may also serve as biomarkers and be used to assess platelet function. We investigated the association between platelet responses to clopidogrel (measured by whole blood impedance aggregometry) and circulating PMVs in patients with acute coronary syndrome (ACS). Blood samples were obtained at discharge from 200 patients with ACS who had undergone percutaneous coronary intervention (PCI). All patients were loaded with aspirin and clopidogrel before PCI. ADP-induced whole blood impedance aggregometry and measurement of PMVs were performed. Cut-off values for HPR and other reactivity (i.e. normal on-treatment reactivity, NPR and low on-treatment reactivity, LPR) to clopidogrel were set according to data from large prospective studies. We measured PMVs as phosphatidylserine and CD42a positive vesicles, together with CD62P or CD40L, using flow cytometry. ADP-induced platelet aggregation revealed that approximately 20% of patients had HPR. Levels of PMVs were almost two-fold higher in the HPR group compared with patients without HPR (for both CD42a- and CD62P-positive PMVs, p  < 0.01). Furthermore, patients with LPR to clopidogrel had significantly fewer PMVs exposing CD62P than patients with HPR or those with NPR to clopidogrel. Patients with HPR during clopidogrel treatment have elevated levels of circulating PMVs, indicating ongoing platelet activation despite clopidogrel treatment. Moreover, in patients with LPR to clopidogrel, circulating PMV numbers are decreased. Taken together, our data suggest that PMVs are potential biomarkers of antiplatelet responses to clopidogrel. If PMVs also have prognostic value after, ACS should be tested in future studies.